Ultrastructural Analysis of Inflammatory Breast Cancer Cell Clusters in an Ex Vivo Environment Mechanically Mimicking the Lymph Vascular System. (December 2021) - Fujii, Yuka; Krishnamurthy, Savitri; El-Zein, Randa
Background: Inflammatory breast cancer (IBC) is a rare form of breast cancer with a poor prognosis. IBC is characterized by florid lymphovascular tumor emboli in the skin and the parenchyma of the breast. We hypothesized that the formation of these emboli/clusters plays a pivotal role in IBC metastasis and its rapid progression, and that their structure and function may be a key to identifying molecular biological differences between IBC and non IBC. Methods: Mechanical methods were used to mimic the lymph fluid viscosity by adding 2.25% of PEG8000 to the media. Clusters were obtained for IBC tumor cell lines (SUM149 and IBC-3), non IBC tumor cell lines (MDA-MB-231, MDA-MB-468, and MCF7), and a non-tumorigenic human mammary epithelial cell line (MCF10A). Clusters were analyzed by light microscopy, and then prepared for and observed by transmission electron microscopy (TEM). Results: Significant differences were seen between IBC and non IBC clusters. The TEM analysis revealed that IBC cells harbored numerous microvilli and microvesicles, both on the free outer surface and inside the cluster. Microvilli from IBC cell clusters were noted at higher density and were longer than those of non IBC cell clusters. Conclusions: IBC tumor cell clusters exhibited distinct ultrastructural features characterized by the presence of long, crowded microvilli and numerous microvesicles. These microvilli may play an important role in the biology and aggressiveness of IBC.